Code generation, analysis tools, and testing for quality - Queirós, Ricardo 1975-; Simões, Alberto 1978-; Pinto, Mário Teixeira 1967- (IGI Global, 2019)
"This book shares new approaches and methodologies for code generation, edition, analysis and testing. It also identifies new trends on these topics, from pedagogical strategies to technological approaches"...